Analysis of Power Quality Issues in Induction Motors. - Nazziwa, Evalyne (Kabale University, 2023)
This project is about the analysis of power quality issues in induction motor machines that was carried out at Kigezi highland tea factory. Power quality problems have been a major concern particularly in this factory, where there are many large-scale type of motor equipment. Thus, it was useful to investigate and mitigate the power quality problems. Assessment of Power quality required the identification of any anomalous behavior on a power system, which adversely affects the normal operation of electrical motors. A power quality assessment involved gathering data resources; analyzing the data (with reference to power quality standards); then, if problems exist, a suitable recommendation or mitigation techniques was considered.